Job search and unemployment insurance: new evidence from time use data - Alan B. Krueger; Andreas Mueller (Institute for the Study of Labor (IZA), 2008)
This paper provides new evidence on job search intensity of the unemployed in the U.S., modeling job search intensity as time allocated to job search activities. The main findings are: 1) the average unemployed worker in the U.S. devotes about 41 minutes to job search on weekdays, which is substantially more than his or her European counterpart; 2) workers who expect to be recalled by their previous employer search substantially less than the average unemployed worker; 3) across the 50 states and D.C., job search is inversely related to the generosity of unemployment benefits, with an elasticity between -1.6 and -2.2; 4) the predicted wage is a strong predictor of time devoted to job search, with an elasticity in excess of 2.5; 5) job search intensity for those eligible for Unemployment Insurance (UI) increases prior to benefit exhaustion; 6) time devoted to job search is fairly constant regardless of unemployment duration for those who are ineligible for UI. A nonparametric Monte Carlo technique suggests that the relationship between job search effort and the duration of unemployment for a cross-section of job seekers is only slightly biased by length-based sampling.
urn:nbn:de:101:1-2008090180
Keywords: J64; 330; Unemployment; unemployment insurance; job search; time use; unemployment benefits; inequality; Arbeitsuche; Arbeitslosigkeit; Dauer; Zeitbudgetforschung; Arbeitslosenversicherung; USA